Development of Competence of Future Teachers as a Pedagogical Problem - Baxronova Marjona San`at qizi (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2024)
any person dreams of seeing the happiness of his child, the perfection of his child to see his achievements , the whole life struggles, to see the achievements of his children, which is the meaning of his life. And in this situation, the role of our highly qualified teachers in the education of our children is incomparable. Through education , the formation of a mentally and intelactulally rich, harmonious generation of our young people, the future of our country, has been carried out. To make the educational process more effective and high-quality is due to the cognitive potential without teachers in itself.